Research on psychotic disorders in rural areas: Recent advances and ongoing challenges. (December 2021) - Peritogiannis, Vaios; Samakouri, Maria
Background: Research on patients with chronic psychotic disorders in rural areas is scarce. Those patients may not receive adequate mental health care. Mental health disparities among rural and urban areas have been recognized. Aims: This review aims to present the most recent research on psychotic disorders in rural areas. Method: We conducted a search in the PubMed and Scopus databases. The search involved articles published over the last decade (2011–2020). All types of research design were included, if studies had used a controlled group of urban patients and reported on the differences among rural/urban residents with psychotic disorders. The focus of the review was on outcome and treatment. Results: A total of 12 studies were included in this review. Most have been conducted in China or India. Reports from Western countries are rare. Outcome studies showed that employment rates are significantly higher in rural patients, as well as rates of marriage in women. It is not clear what is the impact of those outcomes on patients' lives. The finding of lower cost of psychotic disorders in some rural areas, should be viewed with scepticism. Studies on treatment aspects suggested that rural patients were less likely to receive antipsychotics, antipsychotic combination or clozapine. Those results were attributed to limited access to specialized treatment. When rural patients receive specialized community care they seem to have better outcomes than urban patients. Conclusion: There is an ongoing, but still scarce research on patients with chronic psychotic disorders in rural areas. Researchers pointed out the impact of socioeconomic inequalities on outcome and treatment, and stressed the importance of minimizing mental health disparities. These findings may have potential implications for future research; for the introduction of accessible, locally based mental health services in rural areas; and for political initiatives that would address poverty and social inequalities.